SCHEIDEL, WALTER (ED.), THE SCIENCE OF ROMAN HISTORY. BIOLOGY, CLIMATE AND THE FUTURE OF THE PAST, PRINCETON/OXFORD, PRINCETON UNIVERSITY PRESS, 2018. ISBN 978-0-691-16256-0, 260 P. - Csaba Szabó (Journal of Ancient History and Archaeology)
Scheidel, Walter (ed.), The Science of Roman History. Biology, Climate and the Future of the Past, Princeton/Oxford, Princeton University Press, 2018. ISBN 978-0-691-16256-0, 260 p.